## Solving the Equation: (a + 3)(a - 3) - a(a + 5) = 6

This article will walk you through the steps of solving the algebraic equation: **(a + 3)(a - 3) - a(a + 5) = 6**.

### Step 1: Expanding the Equation

We start by expanding the equation using the distributive property:

**(a + 3)(a - 3)**can be expanded as: a² - 3a + 3a - 9 = a² - 9**a(a + 5)**can be expanded as: a² + 5a

Substituting these expansions back into the original equation, we get:

**(a² - 9) - (a² + 5a) = 6**

### Step 2: Simplifying the Equation

Next, we simplify the equation by combining like terms:

a² - 9 - a² - 5a = 6 -5a - 9 = 6

### Step 3: Isolating the Variable

To isolate the variable 'a', we add 9 to both sides of the equation:

-5a - 9 + 9 = 6 + 9 -5a = 15

### Step 4: Solving for 'a'

Finally, we divide both sides by -5 to find the value of 'a':

-5a / -5 = 15 / -5
**a = -3**

Therefore, the solution to the equation **(a + 3)(a - 3) - a(a + 5) = 6** is **a = -3**.